2013
DOI: 10.1108/prog-06-2012-0033
|View full text |Cite
|
Sign up to set email alerts
|

The status of information technology in Iranian hospital libraries

Abstract: PurposeThe purpose of this paper is to compare the attitude of the managers of libraries located at Iran, Tehran and Shahid Beheshti Medical Sciences Universities' training hospitals, on the status of information technology (IT) in the mentioned libraries.Design/methodology/approachThis study employed a researcher‐made questionnaire. The managers of 40 hospital libraries of Iran, Tehran and Shahid Beheshti Universities formed the population of the research. To analyze the collected data, the statistical softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Several studies have been carried out to assess ICT or e-readiness in academic libraries, all of which are related to developing countries. Isfandyari Moghaddam et al (2013) investigated the situation of IT in Iranian hospital libraries from the perspective of managers: the results showed that less than 25 per cent of hospital library managers in Tehran University of Medical Sciences agreed to the application and development of ICT in the library. Several researchers have also examined the e-readiness of academic libraries in Iran and have come to the conclusion that the e-readiness status of most libraries is moderate or lower (Mahdian, 2013; Nematollahi, 2014; Noorafrooz et al , 2012; Norouzi and Jafarpour, 2013; Shahini, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have been carried out to assess ICT or e-readiness in academic libraries, all of which are related to developing countries. Isfandyari Moghaddam et al (2013) investigated the situation of IT in Iranian hospital libraries from the perspective of managers: the results showed that less than 25 per cent of hospital library managers in Tehran University of Medical Sciences agreed to the application and development of ICT in the library. Several researchers have also examined the e-readiness of academic libraries in Iran and have come to the conclusion that the e-readiness status of most libraries is moderate or lower (Mahdian, 2013; Nematollahi, 2014; Noorafrooz et al , 2012; Norouzi and Jafarpour, 2013; Shahini, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%